EVALUASI PROGRAM REHABILITASI SOSIAL DAERAH KUMUH TERHADAP PENINGKATAN KUALITAS HIDUP WARGA DI KELURAHAN NGAGELREJO, KECAMATAN WONOKROMO KOTA SURABAYA - Valeria Ulu; Nihayatus Sholichah (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2020)
Housing and settlements are basic human needs that are important factors in improving human dignity and the quality of a prosperous life in a just and prosperous society. The problem of slums which are mostly inhabited by the poor is a complex and intertwined phenomenon because it has long been a social problem in the community. One of the efforts of the Surabaya City Government to reduce uninhabitable housing is through the Slum Areas Social Rehabilitation Program (RSDK).Research on the Evaluation of the Slum Region Social Rehabilitation Program for Improving the Quality of Life of Residents was carried out to describe the extent of the Evaluation and Impact of the Implementation of the RSDK Program, using descriptive qualitative research methods based on the criteria of Effectiveness, Efficiency, Adequacy, Equality, Responsiveness, and Accuracy. The results of this evaluation indicate that in general, the Program Implementation was sufficient to meet the criteria targeted at the implementation program. In terms of efficiency, program implementation still has shortcomings due to the minimum timeframe specified and also the implementation process that is appropriate to the cost per stage. Adequacy is judged by the success of the development is still low due to complaints from some program beneficiaries. The similarity is seen based on the costs incurred for the Construction of Home Improvements have been carried out fairly. The level of community responsiveness related to program implementation is quite good because of the role of the local community in helping the program implementation process. The accuracy of the program implementation related to the results or program objectives is in accordance with what is desired. The physical impact that occurs with the construction of uninhabitable housing improvement programs can help the development of environmental conditions in the communities living in slums. Meanwhile, the social impact that occurs is to bring up the value that is useful and useful for the needs of people's lives.